Nekaj stalnih, nekaj nevarnih in nekaj težavnih lastnosti rabe frazeologije v medijskih besedilih - Kržišnik, Erika (Teorija in praksa, 2023)
The article presents the use of phraseological units (PUs) in texts about the 2022 Slovenian presidential elections published in three magazines and partly on three web portals. The data are compared with existing data on phraseology in journalistic texts generally. Common characteristics are presented according to the text type, distribution and use of phraseological modifications. The connotation of PUs that reveals the writer's temperament or intention proves to be dangerous. If this connotation is absent, the rational control of expression is revealed. These characteristics of PUs pose a problem when a linguist wants to determine the status and function of a PU.
Keywords: frazemi; Frazeologija; frazeološka prenovitev; journalistic text; Mediji in jezik; medijsko besedilo; modification; modifikacija; phraseme; phraseological modification; phraseology; Slovene language; slovenščina